2015
DOI: 10.1063/1.4922724
|View full text |Cite
|
Sign up to set email alerts
|

Improved linearity in AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors with nonlinear polarization dielectric

Abstract: We demonstrate highly improved linearity in a nonlinear ferroelectric of Pb(Zr0.52Ti0.48)-gated AlGaN/GaN metal-insulator-semiconductor high electron mobility transistor (MIS-HEMT). Distinct double-hump feature in the transconductance-gate voltage (gm-Vg) curve is observed, yielding remarkable enhancement in gate voltage swing as compared to MIS-HEMT with conventional linear gate dielectric. By incorporating the ferroelectric polarization into a self-consistent calculation, it is disclosed that in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…It is observed that the dual gate MOS-HEMT has a more positive threshold voltage of 1.7 V as compared to single gate MOS-HEMT having 0.7 V, which indicates the dependence of the threshold voltage on gate length. The results are also compared with available experimental data [6] of the un-recessed device, which shows negative threshold voltage and larger transconductance. When the gate length is scaled down the effect of electron velocity overshoot is more significant since more number of electrons travel ballistically.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is observed that the dual gate MOS-HEMT has a more positive threshold voltage of 1.7 V as compared to single gate MOS-HEMT having 0.7 V, which indicates the dependence of the threshold voltage on gate length. The results are also compared with available experimental data [6] of the un-recessed device, which shows negative threshold voltage and larger transconductance. When the gate length is scaled down the effect of electron velocity overshoot is more significant since more number of electrons travel ballistically.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, for the dual gate MOS‐HEMT structure, the gate length, gate‐to‐drain spacing, and gate‐to‐gate spacing gate‐to‐source spacing are 0.5, 2.2 μm, 1.6, and 2.2 μm, respectively. A single gate non‐recessed depletion mode ferroelectric MOS‐HEMT is also simulated having the same dimensions of the fabricated device from the literature [6] in order to validate the DC transfer characteristics of the proposed device.…”
Section: Device Structure and Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Linearity improvement at the device level has attracted considerable attention, and significant efforts have been made to enhance device linearity by applying double metal gates (DMGs), fin structures, and transitional recessed gate (TRG) structures and optimizing the epitaxial structure. [12][13][14][15][16][17][18][19][20][21][22][23] The transconductance (g m ) of GaNbased HEMTs decreases quickly with increasing gate voltage after reaching its peak value, which is considered a critical issue for the nonlinearity performance. [17,24] Nonzero derivatives (g 0 m , g 00 m ) of the small-signal DC gain (g m ) caused by the nonlinear nature of the device will produce a large third-order intermodulation amplitude (IMD3) in PAs.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that the flatter transconductance profile results in a lower IM3 levels and a higher third order intercept point (IP3), and thus improves the device linearity. Several methods have been reported in the past to improve the linearity of the GaN HEMTs, including optimizing epitaxial structure 6 10 as gate dielectric. In addition, there have been several reports of monolithic microwave integrated circuit (MMIC) low-noise amplifier (LNA) using GaN dual-gate HEMT devices because the two gates allow higher bias operation and increase the transistor output impedance.…”
mentioning
confidence: 99%